Metals Content in Soils of the Industrial Cities and the Industrial Workshops Area in Riyadh, Saudi-Arabia - Al-Shayeb, S.M. (Asian Journal of Chemistry, 2010)
The metals content (Pb, Zn, Cu, Cr, Ni and Li) of surface and subsurface soils was determined in the first and second industrial cities and the industrial workshops area in Riyadh city. Their levels were investigated in relation to soil depth and the land-use. The levels of Pb, Zn and Cu were found to be elevated in the industrial workshops area and the first industrial city and to a lesser extent in the second industrial city. Lead levels were attributed to the automobile emission whereas Zn and Cu were found to be associated with the industrial activities. Although the second industrial city is newly developed, results of this work have revealed that there are already high Zn, and to a lesser extent Cu, levels at certain locations, where it is recommended that measures to control their release be adopted immediately. Soil profile results showed Pb, Zn and Cu were largely concentrated in the upper surface soils indicating the atmospheric deposition as the main source of such metals.